The housing experience of Hispanic immigrants: the case of Finney, Kansas - Berhanemeskel, Erebecca (Kansas State University, 2017)
Some parts of rural America are experiencing unprecedented demographic and cultural changes as immigrant settlement patterns shift from traditional gateway cities to rural regions that have enticing economic opportunities. In particular, southwest Kansas has become a magnet for immigrant workers and their families. Between 2007 and 2008, Finney County became a majority-minority county (Callebs, 2009). However, lack of affordable housing and limited housing stock has strained communities and become an obstacle for newly settling immigrants (Stull, 2011). This study aims to redress the limited research on immigrants in rural regions and focuses specifically on the cultural experiences of Finney County Hispanic immigrants regarding integration into the local housing community. This qualitative case study is designed using the housing career framework (Murdie, 2002) to capture the factors that influence the housing experience of Hispanic immigrants. The 25 participants were recruited using snowball sampling and convenience sampling techniques. Based on the participant’s language preference, the in-depth interviews were conducted in English or Spanish. This study has found that the mission of community planning has to be a multifaceted process to address the varied needs of immigrant families. Community planners and policy makers can use the information this study provides to better serve the immigrant Hispanic community, which is expected to grow over the coming years.
Keywords: Demographic change; Finney County, KS; Garden City, KS; Hispanic immigrants housing experience; New destination; Somalian immigrants